Pengaruh waktu milling terhadap dan ukuran butir forsterite (Mg2SiO4) mineral serpentin dari Kabupaten Solok Selatan - Sarimai Sarimai (PILLAR OF PHYSICS, 2016)
West Sumatera has great amount of natural mineral resources of serpentine, one of them are found in Jorong Sungai Padi Lubuak Gadang, Kecamatan Sangir, Kabupaten Solok Selatan. The mineral of sepentine contains of forsterite which has higher economical value if it is in form of nano particle. The production of forsterite nano particle has been made by using synthesis substance which is expensive and needs longer process. The variation treatment of temperature calcination toward the mineral of sepentine shows the result that the dominate forsterite is at 800. The mineral of serpentine can be the alternative substance in the production of forsterite particle which is easily found in the nature and is not expensive. The purpose of the research is to investigate the effect of milling time toward size of nano particle of forsterite serpentine mineral in form  of crystal and the size of the particle. The result of the research shows that the effect of milling time toward the micro-structure of forsterite which is viewed by based on the SEM result, it shows that the milling time impacts to the particle size which is the longer milling time, the smaller forsterite particle is produced. The grain size forsterite the lead in milling time 40 hours namely reached 385 nm